2015
DOI: 10.1016/j.urolonc.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Percentage of sarcomatoid component as a prognostic indicator for survival in renal cell carcinoma with sarcomatoid dedifferentiation

Abstract: OBJECTIVE Renal cell carcinoma with sarcomatoid dedifferentiation(sRCC) is associated with higher stage of presentation and worse survival. The objective of this study was to examine the clinicopathological characteristics associated with overall survival(OS), specifically examining the percentage of sarcomatoid component(PSC). METHODS We reviewed clinicopathologic data for all nephrectomized patients with confirmed sRCC. Histologic slides were re-reviewed by dedicated GU pathologists to ascertain PSC. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 24 publications
3
25
1
Order By: Relevance
“…In addition, the vast majority of our patients (92%) presented with symptoms related to their primary tumor or metastatic disease. Consistent with previous reports, 26 our analysis suggested that patients with higher percentages of sarcomatoid component have shorter median OS (Supplementary Figure 4). Detecting sarcomatoid features by biopsy of the primary renal tumor or a metastatic site prior to nephrectomy is challenging.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the vast majority of our patients (92%) presented with symptoms related to their primary tumor or metastatic disease. Consistent with previous reports, 26 our analysis suggested that patients with higher percentages of sarcomatoid component have shorter median OS (Supplementary Figure 4). Detecting sarcomatoid features by biopsy of the primary renal tumor or a metastatic site prior to nephrectomy is challenging.…”
Section: Discussionsupporting
confidence: 92%
“…Tumours consisting only of sarcomatoid cells are placed in the ‘unclassified’ category in the WHO classification [1]. The extent of sarcomatoid morphology has been shown to adversely affect survival, but there is no international agreement on how this can be measured and reported reliably [92, 93]. …”
Section: Resultsmentioning
confidence: 99%
“…We believe that the equivalence of sarcomatoid differentiation and grade 4 classification in RCC may underestimate the prognostic value of sarcomatoid differentiation. Furthermore, Adibi et al [19] found that the percentage of sarcomatoid differentiation (PSD) was a prognostic factor for overall survival in RCC. Zhang et al [20] suggested that PSD was an independent predictor of prognosis.…”
Section: Discussionmentioning
confidence: 99%